Group Counseling as a Means of Strengthening Social Relations of MTs Lab IKIP Al Washliyah Students: A Study with a Behavioral Approach - Nurasyah, Nurasyah; Fitriani, Enny; Putri, Rini Fadhillah; Johannes, Johannes; Muhammadi, Muhammadi (International Journal of Educational Research Excellence, 2025)
The purpose of this study was to determine how group counseling services with a behavioral approach can improve students’ social relationships. The formulation of the research problem is that many students have difficulty in building and maintaining healthy social relationships, which has an impact on their adaptation process in the college environment. The behavioral approach was chosen because it focuses on real behavioral changes through social learning, positive reinforcement, and other measurable techniques. The method used in this study is a quantitative method with a quasi-experimental design using a pre-test and post-test model. The sample of this study used a purposive sampling technique with a sample size of 10 students. The instrument used was a previously validated social relationship questionnaire. The experimental group was given an intervention in the form of group counseling services with a behavioral approach for six sessions. The results of data analysis using the t-test showed that group counseling services with a behavioral approach can improve students’ social relationships. The results of the hypothesis using the t-test obtained from the calculation with the results of t count = 7.626> t table 2.262 that group counseling services with a behavioral approach can improve students’ social relationships.